Preoperative Enteral Nutritional Support in Patients Undergoing Hepatectomy for Hepatocellular Carcinoma: A Strengthening the Reporting of Observational Studies in Epidemiology Article. Issue 46 (November 2015) - Yao, Hui; Bian, Xiaojie; Mao, Liang; Zi, Xuejian; Yan, Xiaopeng; Qiu, Yudong
Abstract : Abstract: To compare the short-term outcomes between hepatocellular carcinoma (HCC) patients with and those without preoperative nutrition on the basis of postoperative enteral nutrition. HCC patients with postoperative enteral nutrition who underwent liver resection between February 2010 and December 2014 in Nanjing Drum Tower Hospital were considered for the study: 43 patients with and 36 patients without preoperative nutrition. Primary endpoint was the incidence of overall complications. Secondary endpoints were infectious and major complications. In the preoperative enteral nutrition group, shorter length of postoperative hospital stay (10.5 ± 2.7 versus 13.7 ± 6.3 days, P = 0.007), less exogenous albumin infusion (10.2 ± 22.4 versus 47.8 ± 97.7 g, P = 0.030), earlier first exhaust time (2.7 ± 0.8 versus 3.0 ± 0.9 days, P = 0.043), and first defection time (3.5 ± 0.9 versus 4.4 ± 1.4 days, P = 0.001) were observed. No significant differences were observed in the incidence of overall complications (32.6% versus 52.8%, P = 0.070), infectious complications (7.0% versus 8.3%, P = 1), and major complications (14.0% versus 11.1%, P = 0.969) between the preoperative enteral nutrition and control group. Preoperative enteral nutrition could improve short-term outcomes of HCC patients via accelerating the recovery of gastrointestinal function and shortening the length of postoperative hospital stay.